Quantitative uptake of colloidal particles by cell cultures - Feliu, Neus; Hühn, Jonas; Zyuzin, Mikhail V.; Ashraf, Sumaira; Valdeperez, Daniel; Masood, Atif; Said, Alaa Hassan; Escudero, Alberto; Pelaz, Beatriz; Gonzalez, Elena; Duarte, Miguel A. Correa; Roy, Sathi; et al. (The science of the total environment, 2016)
The use of nanotechnologies involving nano- and microparticles has increased tremendously in the recent past. There are various beneficial characteristics that make particles attractive for a wide range of technologies. However, colloidal particles on the other hand can potentially be harmful for humans and environment. Today, complete understanding of the interaction of colloidal particles with biological systems still remains a challenge. Indeed, their uptake, effects, and final cell cycle including their life span fate and degradation in biological systems are not fully understood. This is mainly due to the complexity of multiple parameters which need to be taken in consideration to perform the nanosafety research. Therefore, we will provide an overview of the common denominators and ideas to achieve universal metrics to assess their safety. The review discusses aspects including how biological media could change the physicochemical properties of colloids, how colloids are endocytosed by cells, how to distinguish between internalized versus membrane-attached colloids, possible correlation of cellular uptake of colloids with their physicochemical properties, and how the colloidal stability of colloids may vary upon cell internalization. In conclusion three main statements are given. First, in typically exposure scenarios only part of the colloids associated with cells are internalized while a significant part remain outside cells attached to their membrane. For quantitative uptake studies false positive counts in the form of only adherent but not internalized colloids have to be avoided. pH sensitive fluorophores attached to the colloids, which can discriminate between acidic endosomal/lysosomal and neutral extracellular environment around colloids offer a possible solution. Second, the metrics selected for uptake studies is of utmost importance. Counting the internalized colloids by number or by volume may lead to significantly different results. Third, colloids may change their physicochemical properties along their life cycle, and appropriate characterization is required during the different stages.